Making sense of life @ / & SMU: A partial guide for the clueless - PANG, Eng Fong (Institutional Knowledge at Singapore Management University, 2017)
This volume provides unexpectedly heartwarming and heartbreaking insights into the interior lives and thoughts of SMU business graduates. It is both a paean to and an indictment of Singapore’s education system and its excessively powerful formative impact on individual lives, family relationships, and Singapore society as a whole. The youthful contributors overwhelmingly accept life aspirations imposed by the expectations of family, society and self, which they themselves recognise are uniform and limiting. Their intensely personal reflections, unleavened by humour, lay bare the contradictory liberating and homogenising effects of an undergraduate business education (not peculiar to SMU or Singapore only), while refreshingly engaging the too-often-taboo topics of race, religion, sexual orientation and social class.Contents: Keeping Track : Four Years in SMU by Phua Kuan Hua; Growing Up : My Years Before and in SMU by Teo Choon Wei Jonathan; Getting and Staying Ahead by Nicholas Teo; Coping and Managing by Ng Rui Qi; Jumping and Learning by Matthew Goh; Learning Life’s Lessons Since Thirteen by Joanna See Yi Ning; Balancing Work and Life in Five Steps by Stephenie Pang; With Grit, Friends and Family by Lim Ke Hao; Overcoming Setbacks by Nishit Dilip Shah; Making Choices by Choo Teck Li; A Self-Report Card by Max Pang Jing Han; A Rounded Perspective by Lee Peck Khee; The Beauty of Life Experiences by Quek Chui Jin Kenneth; Thirsty at Thirty by Muhamad Hilmi; Turning Points by Aisyah Hanani Binte Mahmud; My First Twenty-two Years by Amanda Tan Kar Mun; A Different Dictionary by Loo Hui Ying Shermaine.“Write Anything” by Vince Tan; My Spice Blend by Brenda Yung; As Told by Me, As Seen by Her by Anonymous; Being and Becoming by Favian Wong; As I Watch Them Age by Chan Yi Ping Rochelle; Life, Death and Life Again by Vani Shriya; Innermost Thoughts by Mabel Lim Qian Hui; Love and Lessons on Friday Mornings by Courtney Kristen Kheng Yin; Captivated by Death by Incognito; Thinking Not So Fast and Relating by Ivan Yong Jiaxiang; In Search of Equanimity by Joel Fan Zhiwen; Examining Life : Muddled Thoughts by Lai Foong Ming; Losing My Inheritance Happily by Arnold Ong; Episodes and Epiphanies by Teo Sheng Hui Bernard; Identity : A Chindian View by Aka; Identity : My Struggle and Search by Joel Tan; Identity : Still Struggling to Make Sense by Nameless.Family and Filial Piety by Hou Chee Peng Mark; 李 Looking Back by Lee Tye Wei; Looking Forward by Sherlyn Cheng; Prologue : To be Continued by Quek Yee Ler; Goodbye : Not a Suicide Note by Puar Si Wei; A Letter to My Future Self by Lim Rui Si; Diamond in the Rough by Joshua Jo; Privilege and Humility by Jasmine Laurence; Just My Luck : Finding Myself Finally by Chua Bao Hui; Why We Shouldn’t Live Our Lives Based on the Fear of Losing Out to Others by Way Yi Ling Samantha; Why We Fight : A Kickboxer’s Corner by Ryan Lee Changwei.Money Suit Social Experiment (1) : Orchard Road by Eugene Peter; Money Suit Social Experiment (2) : Ang Mo Kio by Chan Si Ning Vanessa, Chan Yi Ping Rochelle, Choo Teck Li, Teo Sheng Hui Bernard; Money Suit Social Experiment (3) : Holland Village and Clementi by Chua Bao Hui, Muhammad Danial Bin Yusuf, Oon Chian Yi Gabriel, Teo Choon Wei Jonathan; Cynicism is Easy by Chen Zhan Feng; On Meritocracy, Hard Work and Death by Travis Ng; Japanese Corporate Culture and the Salaryman by Seet Kai Yan Ryan; Wabi Sabi: The Beauty of Impermanence by Tracy Tan; My Take on Stoicism by Marcus Tan Chao Ming; On Inequality by Tan Li Jian.